Efficient Palladium‐Assisted One‐Pot Deprotection of (Acetamidomethyl)Cysteine Following Native Chemical Ligation and/or Desulfurization To Expedite Chemical Protein Synthesis. (29th April 2016) - Maity, Suman Kumar; Jbara, Muhammad; Laps, Shay; Brik, Ashraf
Abstract: The acetamidomethyl (Acm) moiety is a widely used cysteine protecting group for the chemical synthesis and semisynthesis of peptide and proteins. However, its removal is not straightforward and requires harsh reaction conditions and additional purification steps before and after the removal step, which extends the synthetic process and reduces the overall yield. To overcome these shortcomings, a method for rapid and efficient Acm removal using Pd II complexes in aqueous medium is reported. We show, for the first time, the assembly of three peptide fragments in a one‐pot fashion by native chemical ligation where the Acm moiety was used to protect the N‐terminal Cys of the middle fragment. Importantly, an efficient synthesis of the ubiquitin‐like protein UBL‐5, which contains two native Cys residues, was accomplished through the one‐pot operation of three key steps, namely ligation, desulfurization, and Acm deprotection, highlighting the great utility of the new approach in protein synthesis.